Binding of the Molecular Chaperone αB-Crystallin to Aβ Amyloid Fibrils Inhibits Fibril Elongation - Shammas, Sarah L.; Waudby, Christopher A.; Wang, Shuyu; Buell, Alexander K.; Knowles, Tuomas P.J.; Ecroyd, Heath; Welland, Mark E.; Carver, John A.; Dobson, Christopher M.; Meehan, Sarah (Biophysical Society, 2016)
The molecular chaperone αB-crystallin is a small heat-shock protein that is upregulated in response to a multitude of stress stimuli, and is found colocalized with Aβ amyloid fibrils in the extracellular plaques that are characteristic of Alzheimer's disease. We investigated whether this archetypical small heat-shock protein has the ability to interact with Aβ fibrils in vitro. We find that αB-crystallin binds to wild-type Aβ(42) fibrils with micromolar affinity, and also binds to fibrils formed from the E22G Arctic mutation of Aβ(42). Immunoelectron microscopy confirms that binding occurs along the entire length and ends of the fibrils. Investigations into the effect of αB-crystallin on the seeded growth of Aβ fibrils, both in solution and on the surface of a quartz crystal microbalance biosensor, reveal that the binding of αB-crystallin to seed fibrils strongly inhibits their elongation. Because the lag phase in sigmoidal fibril assembly kinetics is dominated by elongation and fragmentation rates, the chaperone mechanism identified here represents a highly effective means to inhibit fibril proliferation. Together with previous observations of αB-crystallin interaction with α-synuclein and insulin fibrils, the results suggest that this mechanism is a generic means of providing molecular chaperone protection against amyloid fibril formation. This study was supported by the Engineering and Physical Sciences Research Council, UK (S.S. and A.K.B.); Unilever and the Biotechnology and Biological Sciences Research Council (C.A.W.); the Wellcome and Leverhulme Trusts (C.M.D.); the Australian Research Council (J.A.C.); the Australian National Health and Medical Research Council; a Peter Doherty Fellowship (H.E.); a Herchel Smith Harvard Postgraduate Scholarship (S.W.); a Royal Society Dorothy Hodgkin Fellowship (S.M.); and a Bye Fellowship, Magdalene College, Cambridge (A.K.B.).